Gender-Sensitive Approaches for the Extractive Industry in Peru : Improving the Impact on Women in Poverty and Their Families - Guide for Improving Practice - Ward, Bernie; Strongman, John; Eftimie, Adriana; Heller, Katherine (World Bank, Washington, DC, 2014)
In the companion report to this guide, gender-sensitive approaches to the extractive industry in Peru: improving impacts on women in poverty and their families, ward and strongman present solid, evidence-based arguments leading to the conclusion that Extractive Industry (EI) companies could significantly improve their sustainable development impact on women and families by making some practical and simple changes in their working practices. The report also provides extensive evidence of weaknesses in company and government policies and practices that contribute to a previously under recognized issue: men are capturing more of the benefits of EI projects, which are not necessarily reaching the wider family; while women and children experience more of the risks that arise from EI projects.